SOSIALISASI PENCEGAHAN PERUNDUNGAN DALAM UPAYA MEWUJUDKAN SEKOLAH RAMAH ANAK - Noya, Andris; Kiriwenno, Erlin (Universitas Mataram, 2024)
Bullying is a social phenomenon that often occurs in the school environment. Most students have experienced bullying either as victims, perpetrators, or as people who witnessed the incident. This phenomenon needs to be addressed by related parties in prevention efforts. One activity that can be carried out is outreach to students at school about bullying prevention. This community service activity was carried out at SMP Negeri 7 Ambon. The aim of this activity is for participants to understand what bullying is, the types of bullying and the impact of bullying behavior. Participants are also invited not to carry out bullying in the school environment. The methods used in this activity are lectures, discussions and educational games using the Kahoot application. The team also conducted a survey regarding bullying at school using the Retrospective Bullying Questionnaire. Community service activities in the form of outreach about bullying prevention are running well and effectively. The final results of this activity show a positive response from students regarding efforts to prevent bullying in schools in creating child-friendly schools. Child-friendly schools can be created when school residents are not involved in bullying.